2019
DOI: 10.1186/s13039-019-0451-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive prenatal testing reveals copy number variations related to pregnancy complications

Abstract: Background Pregnancy complications could lead to maternal and fetal morbidity and mortality. Early diagnosing and managing complications have been associated with good outcomes. The placenta was an important organ for development of pregnancy complications. Thus, non-invasive prenatal testing technologies could detect genetic variations, such as aneuploidies and sub-chromosomal copy number variations, reflecting defective placenta by maternal plasma cffDNAs. Maternal cffDNAs had been proved to der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…We annotated 2190 genes in the window regions ( Supplementary Table 2 ). The previously discovered alpha- and beta-defensin genes, DEFA1, DEFA3 and DEFB1 [ 22 ], also occurred in our gene list.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…We annotated 2190 genes in the window regions ( Supplementary Table 2 ). The previously discovered alpha- and beta-defensin genes, DEFA1, DEFA3 and DEFB1 [ 22 ], also occurred in our gene list.…”
Section: Resultsmentioning
confidence: 70%
“…A study with cfDNA had identified CNVs in three chromosome regions related to a high risk of GDM. Gene enrichment analysis reveals that the genes in these regions contain some alpha- and beta-defensin family members, such as DEFA1, DEFA3 and DEFB1, copy number variations of which are associated with type I and II diabetes [ 22 ]. However, there are no existing methods for early prediction of GDM based on the CNV markers.…”
Section: Introductionmentioning
confidence: 99%
“… 13 The questionnaire contains demographic information related to age, native language, educational level, gestational week, parity and previous miscarriages as well as multiple choice and Likert scale questions related to their attitudes, knowledge, choice of information related to risk and decision-making of prenatal testing including the NIPT. 7 The attitudes regarding delivering a baby with a chromosomal defect, and the self-estimated probability of the event, was included in the assessment items.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Non-invasive prenatal testing is a cell-free DNA test involving the isolation of fetal DNA from a maternal plasma sample. 7 The cell-free DNA is from a placental origin, released in the maternal circulation from the fetal apoptotic trophoblasts. 8 The release of fetal DNA fragments in maternal circulation increases with gestational age and the reliability of testing is more than 10% as early as 10 weeks gestation.…”
mentioning
confidence: 99%
“…Therefore, it is important to provide health education regarding the aim of prenatal anomaly screening and its possibilities through medical expertise. In countries offering prenatal anomaly screening, medical counsellors are easily interpreted as exponents of (medical) society, usually focusing primarily on the advantage of screening to detect an anomaly to manage or monitor pregnancy outcomes [11,[16][17][18][19]. However, parents might have other motivations for both attending counselling and/or entering prenatal screening programmes [20].…”
mentioning
confidence: 99%